Hidden in plain sight: a morphological study revealing three new species of the skipper genus Drephalys Watson, 1893 (Lepidoptera: Hesperiidae) from Brazil - Siewert, Ricardo Russo; Madruga, Janaína; Dolibaina, Diego Rodrigo; Mielke, Olaf Hermann Hendrik; Casagrande, Mirna Martins (Zootaxa, 2018)
Three new species of Drephalys Watson, 1893 from Brazil are described as follows: D. dracarys Madruga, Siewert, Mielke & Dolibaina, sp. n. from Acre, Mato Grosso and Rondônia states, D. electrinus Siewert, Madruga, Mielke & Dolibaina, sp. n. from Acre and Amazonas states, and D. citrinus Madruga, Siewert, Mielke & Casagrande, sp. n. from Amazonas state. Drephalys heraclides Bell, 1942 was reported for the first time from Brazil. To characterize the new species, illustrations of the male genitalia of D. heraclides, D. phoenice (Hewitson, 1867) and D. phoenicoides (Mabille & Boullet, 1919) are provided. Diagnosis, adult photos, illustration of the male genitalia and a geographical distribution map are provided for the new species.